Предиктори раннього клініко-неврологічного погіршення у пацієнтів в гострому періоді спонтанного супратенторіального внутрішньомозкового крововиливу - Козьолкін, Олександр Анатолійович; Кузнєцов, Антон Анатолійович; Kozyolkin, O. A.; Kuznietsov, A. A. (My University, 2020)
Мета роботи - удосконалити діагностичні заходи в гострому періоді спонтанного супратенторіального внутрішньомозкового крововиливу шляхом розробки критеріїв прогнозування раннього клініко-неврологічного погіршення на тлі консервативної терапії. Матеріали і методи. Проведено проспективне дослідження з залученням 339 хворих на геморагічний півкульовий інсульт, що розвинувся вперше. Клініко-неврологічне обстеження здійснювали в динаміці перебігу гострого періоду захворювання з використанням шкали коми Full Outline of UnResponsiveness та National Institute of Health Stroke Scale. За даними нейровізуалізації визначали обсяги внутрішньомозкового та вторинного внутрішньошлуночкового крововиливів, наявність та вираженість латеральної дислокації серединних структур мозку. В якості кумулятивної кінцевої точки було обрано раннє клініко-неврологічне погіршення, за яке вважали один або декілька з наведених нижче подій, що виникли на тлі консервативної терапії протягом 24/48 годин з моменту госпіталізації: зниження сумарного балу за шкалою коми Full Outline of UnResponsiveness ≥2; збільшення сумарного балу за National Institute of Health Stroke Scale ≥4; летальний вихід. Для розробки критеріїв прогнозування використовували логістичний регресійний аналіз та ROC-аналіз. This study was designed in order to improve diagnostic approaches in acute period of spontaneous intracerebral haemorrhage based on the elaboration of prognostic criteria for detecting early neurological deterioration under the conservative treatment. This prospective study included 339 patients having the first intracerebral haemorrhage. Clinical neurological examinations were carried out over the course of acute period of the disease by using Full Outline of UnResponsiveness scale and National Institute of Health Stroke Scale. The volume of intracerebral and secondary intraventricular haemorrhage, presence and severity of midline shift were detected by neurovisualizing techniques. Early neurological deterioration was chosen as a cumulative endpoint. We considered the signs of deterioration under the therapy during the first 24 – 48 hours following the admission to the hospital: decrease in Full Outline of UnResponsiveness scale score ≥2; increase in the National Institute of Health Stroke Scale score ≥4; lethal outcome. Logistic regressive analysis and ROC-analysis were used for elaboration of the prognostic criteria. Results. Neurological deterioration under the conservative therapy for 24 – 48 hours since the hospitalization was detected in 29,2-33,6% of cases. Multiple logistic regression analysis showed that initial degree of midline shift and volume of secondary intraventricular haemorrhage are the most informative parameters for evaluating risk of early neurological deterioration in patients with hemorrhagic stroke, who received the conservative therapy.
Predictors of early neurological deterioration in patients with acute spontaneous supratentorial intracerebral haemorhage
Keywords: внутрішньомозковий крововилив; раннє клініко-неврологічне погіршення; прогноз; intracerebral haemorrhage; early neurological deterioration; prognosis